Seruan Paulus Hanya Satu Injil Yang Benar (Studi Eksegetis Galatia 1:6-10) Dan Refleksi Teologisnya - Arta Sary Saragih; Herdiana Boru Hombing S; Robert Juni Tua Sitio (Student Research Journal, 2023)
This research aims to examine and analyze Paul's call about only one true Gospel in Galatians 1:6-10 by identifying the problematic conditions that occurred in the Galatians by interpreting Galatians which then focuses on the main problem of the text which is limited by the author. In this writing the author uses an exegetical method with a syntactic and semantic approach to text analysis by focusing on the text itself, but does not rule out other texts from the Bible as well as various library sources, books, journals which also discuss related topics. So, through this method, the author has found and can know what the Apostle Paul called for, namely that only one Gospel is true (Galatians 1:6-10). The results of this research reveal that Paul firmly called on the Galatians that only one true Gospel is the news of God's word about God's gift of salvation, namely the content of the message is that salvation is sufficient because the death and resurrection of Jesus Christ is the absolute cause of eternal salvation for everyone. Not because there is an addition to carrying out all the Mosaic Torah and the Jewish tradition of circumcision or mixing human efforts, even other doctrines that claim to be from angels or otherwise subtracting from the Gospel of Christ which God prepared for salvation. Paul emphasized that it was God who planned human salvation based on God's initiative, driven by Himself and human conversion was God's work, where God was the one who carried out that salvation, starting from planning, preparing and preaching to giving it to humans so they could be saved for free. unconditionally, namely wanting to believe in the preaching of the Gospel of Christ and accepting the good news that only the Lord Jesus is the savior of mankind. Through studying the exegetical analysis of Galatians 1:6-10, the author realizes that the conditions and cases in the Galatian congregation are very relevant for believers today and it is hoped that this writing can be a reflection for believers to be careful and firm about whether the content of the Gospel message is in accordance with the true Gospel. The Bible preaches both salvation sermons, fellowship, similar teachings that are widely circulated which claim to be the true Gospel.